CONSTRUCTION OF SKEW CYCLIC CODES OVER Fq + vFq - Gursoy, Fatmanur; Siap, Irfan; Yildiz, Bahattin (AMER INST MATHEMATICAL SCIENCES-AIMS, 2014)
In this paper skew cyclic codes over the the family of rings Fq + vFq with v(2) = v are studied for the first time in its generality. Structural properties of skew cyclic codes over Fq + vFq are investigated through a decomposition theorem. It is shown that skew cyclic codes over this ring are principally generated. The idempotent generators of skew-cyclic codes over Fq and Fq + vFq have been considered for the first time in literature. Moreover, a BCH type bound is presented for the parameters of these codes.
Keywords: Skew polynomial rings; skew cyclic codes; codes over rings; Computer Science; Mathematics